Nan-Ching : The Classic of Difficult Issues. - Unschuld, Paul U. (Berkeley : University of California Press, 2022)
Although the study of traditional Chinese medicine has attracted unprecedented attention in recent years, Western knowledge of it has been limited because, until now, not a single Chinese classical medical text has been available in a serious philological translation. The present book offers, for the first time in any Western language, a complete translation of an ancient Chinese medical classic, the Nan-ching. The translation adheres to rigid sinologic.
Description based upon print version of record.
JSTOR
Keywords: Medicine, Chinese -- Early works to 1800.; Médecine chinoise -- Ouvrages avant 1800.; HISTORY / Indigenous Peoples of the Americas; Medicine, Chinese; Early works